Identification and Behavioral Evaluation of Sex Pheromone Components of the Chinese Pine Caterpillar Moth, Dendrolimus tabulaeformis - Kong, Xiang-Bo (Public Library of Science, 2012)

(untitled)
BACKGROUND: The Chinese pine caterpillar moth, Dendrolimus tabulaeformis Tsai and Liu (Lepidoptera: Lasiocampidae) is the most important defoliator of coniferous trees in northern China. Outbreaks occur over enormous areas and often lead to the death of forests during 2–3 successive years of defoliation. The sex pheromone of D. tabulaeformis was investigated to define its chemistry and behavioral activity. METHODOLOGY/PRINCIPAL FINDINGS: Sex pheromone was collected from calling female D. tabulaeformis by headspace solid phase microextraction (SPME) and by solvent extraction of pheromone glands. Extracts were analyzed by coupled gas chromatography/mass spectrometry (GC-MS) and coupled GC-electroantennographic detection (GC-EAD), using antennae from male moths. Five components from the extracts elicited antennal responses. These compounds were identified by a combination of retention indices, electron impact mass spectral matches, and derivatization as (Z)-5-dodecenyl acetate (Z5-12:OAc), (Z)-5-dodecenyl alcohol (Z5-12:OH), (5Z,7E)-5,7-dodecadien-1-yl acetate (Z5,E7-12:OAc), (5Z,7E)-5,7-dodecadien-1-yl propionate (Z5,E7-12:OPr), and (5Z,7E)-5,7-dodecadien-1-ol (Z5,E7-12:OH). Behavioral assays showed that male D. tabulaeformis strongly discriminated against incomplete and aberrant blend ratios. The correct ratio of Z5,E7-12:OAc, Z5,E7-12:OH, and Z5,E7-12:OPr was essential for optimal upwind flight and source contact. The two monoenes, Z5-12:OAc and Z5-12:OH, alone or binary mixtures, had no effect on behavioral responses when added to the optimal three-component blend. CONCLUSIONS/SIGNIFICANCE: The fact that deviations from the optimal ratio of 100∶100∶4.5 of Z5,E7-12:OAc, Z5,EZ7-12:OH, and Z5,E7-12:OPr resulted in marked decreases in male responses suggests that biosynthesis of the pheromone components is precisely controlled. The optimal blend of the sex pheromone components of D. tabulaeformis worked out in this study should find immediate use in monitoring this pest in Chinese forests.